Bahia et la réponse du peuple - Tahar Chikhaoui (Revue des Mondes Musulmans et de la Méditerranée)
What do the Arab revolutions say on film making? The question is all the more interesting than images had never before, in the Arab world at large, played such a decisive role in socio-political upheavals. Small cameras were used as arms against dictatorships and diffusion through social networks of images taken with these cameras had a significant impact. The history of cinema seemed to suddenly accelerate. In retrospect, politically-motivated films made ​​since the seventies, have become distant with time and those more personal produced in the 1980s, 1990s and 2000s seem completely out of sync with reality. Through a study of unseen, complex relations, constantly shifting between the mode of expression of cinematic art and the logic in the evolution of socio-political events, we became aware of the confusing optical illusions caused by the acceleration of history and growing interweaving of political, social, cultural and technological factors. By further examining the nature of the recent developments in the history of the Arab world, the acceleration of the modes of cultural and political representation, we better understood the film art position and the necessary distinction between different types, natures and functions of images spread around. Therefore, we better understand the challenges ahead; in any case, we manage to see more clearly into the situation.